COVID‐19 Vaccine Response in People with Multiple Sclerosis - Tallantyre, Emma C.; Vickaryous, Nicola; Anderson, Valerie; Asardag, Aliye Nazli; Baker, David; Bestwick, Jonathan; Bramhall, Kath; Chance, Randy; Evangelou, Nikos; George, Katila; Giovannoni, Gavin; Godkin, Andrew; et al. (Annals of neurology, 2022)
Objective The purpose of this study was to investigate the effect of disease modifying therapies on immune response to severe acute respiratory syndrome‐coronavirus 2 (SARS‐CoV‐2) vaccines in people with multiple sclerosis (MS). Methods Four hundred seventy‐three people with MS provided one or more dried blood spot samples. Information about coronavirus disease 2019 (COVID‐19) and vaccine history, medical, and drug history were extracted from questionnaires and medical records. Dried blood spots were eluted and tested for antibodies to SARS‐CoV‐2. Antibody titers were partitioned into tertiles with people on no disease modifying therapy as a reference. We calculated the odds ratio of seroconversion (univariate logistic regression) and compared quantitative vaccine response (Kruskal Wallis) following the SARS‐CoV‐2 vaccine according to disease modifying therapy. We used regression modeling to explore the effect of vaccine timing, treatment duration, age, vaccine type, and lymphocyte count on vaccine response. Results Compared to no disease modifying therapy, the use of anti‐CD20 monoclonal antibodies (odds ratio = 0.03, 95% confidence interval [CI] = 0.01–0.06, p < 0.001) and fingolimod (odds ratio = 0.04; 95% CI = 0.01–0.12) were associated with lower seroconversion following the SARS‐CoV‐2 vaccine. All other drugs did not differ significantly from the untreated cohort. Both time since last anti‐CD20 treatment and total time on treatment were significantly associated with the response to the vaccination. The vaccine type significantly predicted seroconversion, but not in those on anti‐CD20 medications. Preliminary data on cellular T‐cell immunity showed 40% of seronegative subjects had measurable anti‐SARS‐CoV‐2 T cell responses. Interpretation Some disease modifying therapies convey risk of attenuated serological response to SARS‐CoV‐2 vaccination in people with MS. We provide recommendations for the practical management of this patient group. ANN NEUROL 20219999:n/a–n/a